2009
DOI: 10.1002/etc.27
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressants and their metabolites in municipal wastewater, and downstream exposure in an urban watershed

Abstract: Antidepressants are a widely prescribed group of pharmaceuticals that can be biotransformed in humans to biologically active metabolites. In the present study, the distribution of six antidepressants (venlafaxine, bupropion, fluoxetine, sertraline, citalopram, and paroxetine) and five of their metabolites was determined in a municipal wastewater treatment plant (WWTP) and at sites downstream of two WWTPs in the Grand River watershed in southern Ontario, Canada. Fathead minnows (Pimephales promelas) caged in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
239
3
14

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 434 publications
(266 citation statements)
references
References 36 publications
10
239
3
14
Order By: Relevance
“…2009)) have known negative effects on aquatic and marine organisms (e.g., Fong & Molnar, 2008; Metcalfe et al., 2010; Meredith‐Williams et al, 2012; Gaw et al., 2014). Our study and others have assessed the effects of single pharmaceuticals on animal behavior and their potential to alter species interactions (Bossus et al., 2014; Gaworecki & Klaine, 2008; Hazelton et al., 2013; Piggott, Baldwin, Dissanayake, & Sloman, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2009)) have known negative effects on aquatic and marine organisms (e.g., Fong & Molnar, 2008; Metcalfe et al., 2010; Meredith‐Williams et al, 2012; Gaw et al., 2014). Our study and others have assessed the effects of single pharmaceuticals on animal behavior and their potential to alter species interactions (Bossus et al., 2014; Gaworecki & Klaine, 2008; Hazelton et al., 2013; Piggott, Baldwin, Dissanayake, & Sloman, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Pharmaceutical compounds and their derivatives regularly enter estuaries and near‐shore coastal ecosystems via transport of contaminated surface and groundwater runoff, suspended river sediments, and untreated sewage effluent (Bringolf et al., 2010; Khairy, Weinstein, & Lohmann, 2014; Metcalfe et al., 2010). These compounds are designed to illicit biological responses as medical drugs and could have considerable effects on organism health, despite detections at low concentrations (Ankley, Brooks, Huggett, & Sumpter, 2007; Seiler, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Out of the administered amount, 92% is recovered in urine, as the renal excretion pathway is prevailing. However, VFA in urine appears in only 5% (1-10% [10]), unconjugated O-desmethyl Venlafaxine (29%), conjugated O-desmethyl Venlafaxine (26%), 1% N-desmethyl Venlafaxine, and the rest as the other intermediates. Hence, a normal person excretes $2 L urine per day, it is normal to expect lg/L concentrations in patients.…”
Section: Experiments In Real Secondary Wastewater Effluents and Humanmentioning
confidence: 99%
“…Chemically, it belongs to the class of benzene and substituted derivatives and is a tertiary amino compound that is N,N-dimethylethanamine substituted at position 1 by a 1-hydroxycyclohexyl and 4-methoxyphenyl group (Table 1). Its excretion from the body follows the renal route, ends up in WWTPs, and therefore it is found in natural waters as VFA, plus its metabolites are escaping in almost 50% rate the wastewater treatment process [9][10][11][12]. Measured concentrations range from 18 to 122 ng L À1 for VFA [13], or 102 and 690 ng L À1 [11,14] which could affect the natural biota.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that paroxetine and its metabolites [1][2][3] have the potential to accumulate in waste waters, 4 but also in the tissue of fish 5 as a result of discharges of this antidepressant into surface waters from municipal wastewater treatment plants. 6,7 Environmental risk assessment of paroxetine has been performed earlier, but only the parent (3S,4R)-(4-(4′-fluorophenyl)-3-(3,4-methylenedioxyphenoxymethyl)piperidine (I) and its major human metabolite trans-4-[4-(4′-fluorophenyl)-3-piperidinylmethoxy]-2-methoxyphenol (II) have been considered (Scheme 1) in more detail. 8 According to ecotoxicity results, paroxetine itself should not exert any significant effects on aquatic organisms.…”
Section: Introductionmentioning
confidence: 99%